Dynamic relocation of PKA regulatory subunits during sperm capacitation: Linking PKA to the CatSper signaling complex - Analia G. Novero; Arturo Matamoros-Volante; Lucila R. Gomez-Olivieri; Cintia Stival; Guillermina M. Luque; Alan M. Szalai; Andrea L. Ambrosio; Fernando D. Stefani; Mariano G. Buffone; Dario Krapf; Diego Krapf (Proceedings of the National Academy of Sciences, 2025)
To fertilize an oocyte, mammalian spermatozoa must undergo a maturation step known as capacitation that takes place after ejaculation. Protein kinase A (PKA) plays a fundamental role in capacitation in all mammalian species. Before capacitation, PKA is maintained in an inactive state where the catalytic subunits are bound to a dimer of inhibitory regulatory subunits. A key element in the regulation of PKA lies in its intracellular compartmentalization achieved by docking at A-kinase anchoring proteins (AKAP). Despite the crucial role of the modulation of local PKA activity in fertilization, its localization and mechanism of compartmentalization are not well understood. Here, we approach this problem using quantitative laser scanning microscopy and superresolution imaging to dissect the interactions and relocalization of PKA subunits during capacitation. We find that in the resting state, both catalytic and regulatory subunits colocalize close to the axoneme. Upon capacitation, the PKA regulatory subunits, but not the catalytic subunits, relocate to a quadrilateral structure along the flagellum principal piece, in the vicinity of AKAP4 and the CatSper channel signaling complex. Furthermore, this quadrilateral localization of PKA regulatory subunits disappears in sperm from CatSper1 knockout mice. The sharp difference between the localization of PKA regulatory subunits in capacitated vs. noncapacitated sperm cells demonstrates its suitability as a biomarker for identifying capacitation, an enduring problem in the study of sperm physiology.